Literature Review: Effectiveness of Chest CT for Triage in the Emergency Departmet (ED) in Patients with Suspected COVID-19 - Aniq Lutfiyah; Iwan Purnawan; Ridlwan Kamaluddin (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background: COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. The spread of this virus is very fast, so patients come to the Emergency Department (ED) for examination. The initial examination was carried out by triage the patient using the RT-PCR method. Then, there are recent studies that Computed Tomography (CT) can be used as a triage tool and help in the early diagnosis of patients with suspected COVID-19. Objectives: To determine chest CT for triage in the Emergency Department (ED) in patients with suspected COVID-19. Method:Search for articles was conducted electronically using Google Scholar, Sience Direct, and PubMed databases. Article used from March 2020 to January 2021. Keywords in this article search used the keywords